A Decoy-Receptor Approach Using Nicotinic Acetylcholine Receptor Mimics Reveals Their Potential as Novel Therapeutics Against Neurotoxic Snakebite - Albulescu, Laura-Oana; Kazandjian, Taline; Slagboom, Julien; Bruyneel, Ben; Ainsworth, Stuart; Alsolaiss, Jaffer; Wagstaff, Simon C.; Whiteley, Gareth; Harrison, Robert A.; Ulens, Chris; Kool, Jeroen; Casewell, Nicholas R. (Frontiers in Pharmacology, 2019)
Snakebite is a neglected tropical disease that causes 138,000 deaths each year. Neurotoxic snake venoms contain small neurotoxins, including three-finger toxins (3FTxs), which can cause rapid paralysis in snakebite victims by blocking postsynaptic transmission via nicotinic acetylcholine receptors (nAChR). These toxins are typically weakly immunogenic and thus are often not effectively targeted by current polyclonal antivenom therapies. We investigated whether nAChR mimics, also known as acetylcholine binding proteins (AChBPs), could effectively capture 3FTxs and therefore be developed as a novel class of snake-generic therapeutics for combatting neurotoxic envenoming. First, we identified the binding specificities of 3FTx from various medically-important elapid snake venoms to nAChR by using two recombinant nAChR mimics: the AChBP from Lymnaea stagnalis and a humanized neuronal α7 version (α7-AChBP). We next characterized these AChBP-bound and unbound fractions using SDS-PAGE and mass spectrometry. Interestingly, both mimics effectively captured long-chain 3FTxs from multiple snake species, but largely failed to capture the highly related short-chain 3FTxs, suggesting a high level of binding specificity. We next investigated whether nAChR mimics could be used as snakebite therapeutics. We showed that while α7-AChBP alone did not protect against Naja haje (Egyptian cobra) venom lethality in vivo, it significantly prolonged survival times when coadministered with a nonprotective dose of antivenom. Thus, nAChR mimics are capable of neutralizing specific venom toxins and may be useful adjunct therapeutics for improving the safety and affordability of existing snakebite treatments by reducing therapeutic doses. Our findings justify exploring the future development of AChBPs as potential snakebite treatments.